La boulangère de Monceau - Rohmer, Éric; Barbey, Bruno; Meurice, Jean-Michel; Schroeder, Barbet; Soubrier, Claudine; Girardon, Michèle (Potemkine Films, 2013)
In "The Girl at the Monceau Bakery" (La boulangère de Monceau), the protagonist is a young man (Barbet Schroeder, Rohmer's producer at the time and soon to be a director in his own right). The young man is infatuated by Sylvie (Michèle Girardon), whom he sees walking past every day. When he doesn't see her for some time, he asks the girl at the bakery, Jacqueline (Claudine Soubrier) to go out with him. Then he is faced with a dilemma when he arranges a date with Sylvie for the same time. "Monceau" is under half an hour long, but many of Rohmer's stylistic traits and themes are already in place. The use of voiceover is one, but what the young man tells us is not necessarily to be taken at face value. Rohmer always views his characters with an ironic distance, men especially, and what the voiceover says does not always tally with what we see on screen. The young man overstates the two women's reactions to him, and ultimately he is not very likeable. [www.thedigitalfix.com]
Keywords: Blu-Ray-Disc